The Relationship Between Body Mass Index (BMI) and the Occurrence of Gastroesophageal Reflux Disease (GERD) Among Students of the Faculty of Medicine, Universitas Sumatera Utara, Batch of 2021 and 2022 - Dimas Zainuddin Amir; M. Aron Pase; Melvin Nova Gunawanto Barus; Adriansyah Lubis (Talenta Publisher, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a common digestive disorder, especially among young adults like college students. One factor linked to GERD is Body Mass Index (BMI). Although higher BMI is associated with a greater risk of GERD, limited data exists on this relationship in university populations, particularly at the Faculty of Medicine, Universitas Sumatera Utara. Objective: This study aims to analyze the relationship between BMI and GERD incidence in FK USU students from the 2021 and 2022 batches. Methods: An analytical, cross-sectional study was conducted using simple random sampling. The subjects were Medical Education students from the 2021 and 2022 batches. Data collection was done through direct distribution of the GERD-Q questionnaire. Statistical analysis included univariate and bivariate methods using chi-square tests. Results: Among 100 respondents, 52 (52.0%) had GERD. Among those with GERD, 43 (29.6%) were obese and 9 (22.4%) had normal BMI. Of those without GERD, 34 (20.6%) had normal BMI and 14 (27.4%) were obese. A significant relationship was found between BMI and GERD (p = 0.011). Conclusion: There is a significant relationship between BMI and GERD incidence among FK USU Medical Faculty students from the 2021–2022 batches.